An evaluation of a FRIENDS for Life programme in a mainstream secondary school and its impact on emotional distress, anxiety and coping skills - Green, Sarah L. (2013)
‘FRIENDS for Life’ is a manualised, 10 week, Cognitive Behavioural Therapy (CBT) based programme designed to be run in school and community settings (Barrett, 2010b). The programme has been introduced to schools within the local authority where the researcher is based via the local Targeted Mental Health in Schools (TAMHS) project. The programme is well reviewed and is recommended by the World Health Organisation for the treatment of anxiety disorders in children (World Health Organisation, 2004). Previous research has evaluated the programme when delivered in closely monitored situations with optimal implementation. The aim of this study is to evaluate the impact of FRIENDS for Life as implemented in a mainstream secondary school by school staff trained as part of the TAMHS initiative. This study makes an original contribution to the existing research base by evaluating the programme in a naturalistic, real world setting using an alternative methodology to the majority of published evaluations. Data regarding implementation of the programme was collected and analysed using activity theory. A single case experimental design was used to monitor the impact of the intervention on the emotional distress, anxiety levels and coping strategies of 5 secondary school participants (aged 11-13) who had been identified by school staff as appearing anxious. The findings suggest that participation in FRIENDS did not result in the hypothesised reductions in emotional distress, anxiety and negative coping skills or the hypothesised improvement in active coping skills. These results are discussed with regard to the finding that some aspects of the programme were not delivered. Analysis of the context using activity theory suggested that factors such as lack of time, space for delivery and experience and training impacted upon implementation. Methodological issues contributing to these findings are considered and implications for the local TAMHS project and for Educational Psychologists are discussed.